1987
DOI: 10.1002/1097-0142(19870915)60:6<1378::aid-cncr2820600636>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of developing acute leukemia after employment as a painter

Abstract: A case-control interview study of 125 adult patients with acute leukemia and 125 controls matched with respect to age (-+ four years), sex, and residence was carried out in central Sweden during the period from September 1980 to May 1983. Their history of organic solvent exposure is described. A significant overrisk of developing acute leukemia was found when comparison between patients and controls revealed a difference in the solvent exposure rate, which was significantly higher in patients than in controls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 26 publications
(1 reference statement)
2
19
0
Order By: Relevance
“…They are largely composed of saturated hydrocarbons (or alkanes, which in liquid form are C5–C17), but also include a small proportion of benzene. Although benzene is a recognized leukemogenic agent [International Agency for Research on Cancer (IARC) 1987], there is little information on the carcinogenicity of mineral spirits as such; a Swedish study reported an increased risk of acute leukemia among painters (Lindquist et al 1987), but painters may be exposed to a greater extent to other solvents such as toluene and xylene. Leaded gasoline, another mixture that showed indications of increasing risk, is a mixture of hydrocarbons used as fuel for automobiles; it also contains benzene and toluene.…”
Section: Discussionmentioning
confidence: 99%
“…They are largely composed of saturated hydrocarbons (or alkanes, which in liquid form are C5–C17), but also include a small proportion of benzene. Although benzene is a recognized leukemogenic agent [International Agency for Research on Cancer (IARC) 1987], there is little information on the carcinogenicity of mineral spirits as such; a Swedish study reported an increased risk of acute leukemia among painters (Lindquist et al 1987), but painters may be exposed to a greater extent to other solvents such as toluene and xylene. Leaded gasoline, another mixture that showed indications of increasing risk, is a mixture of hydrocarbons used as fuel for automobiles; it also contains benzene and toluene.…”
Section: Discussionmentioning
confidence: 99%
“…No evidence of smokeless tobacco risks was apparent in a single study of acute leukemia from a Swedish case-control study (Lindquist et al, 1987). Cervical cancer was linked to smokeless tobacco use by women in a study based on cancer patients from the Third National Cancer Survey (Williams and Horm, 1977); interestingly, human papillomaviruses are suspected to play a role in both cervical and oral cancer (Yeudall, 1992;Schiffman and Brinton, 1995).…”
Section: Other Cancersmentioning
confidence: 99%
“…Employment in many industries and occupations has been associated with leukemia including agriculture [Blair and Zahm, 1995;Kristensen et al, 1996;Cerhan et al, 1998], oil re®ning and petrochemicals [Jarvholm et al, 1997;Divine et al, 1999], construction [Robinson et al, 1995, and the nuclear industry or weapons production [Kendall et al, 1992;Cardis et al, 1995]. Elevated risk of leukemia has also been observed among nurses and other healthcare workers [Peipins et al, 1997;Burnett et al, 1999;Petralia et al, 1999], electric utility workers [London et al, 1994;Floderus et al, 1999], vehicle mechanics [Hunting et al, 1995], managers and professionals [Loomis and Savitz, 1991], hairdressers [Miligi et al, 1999], shoe manufacturing workers [Bulbulyan et al, 1998], painters and printers [Lloyd et al, 1977;Lindqvist et al, 1987], welders and embalmers, anatomists, and pathologists [Linos et al, 1989;Hayes et al, 1990).…”
Section: Introductionmentioning
confidence: 99%